Možnosti zvyšování efektivnosti veřejného sektoru v podmínkách krize veřejných financí II - Malý, Ivan (Masaryk University Press, 2020)
Title in English: Improving Public Sector Efficiency in Times of Public Finance Crisis This publication is the summary of results of free selected PhD theses prepared by students from ESF MU, dealing with two very actual topics: - the analysis of impact from introducing heath care fees in the Czech Republic (Krutilova), - efficiency of taxation - administrative and compliance costs (Pompura, Cizmarik).